Reaching Algebra Readiness (RAR) - Williams, Tony G. author. aut Link
X, 171 p.
Keywords: Research has shown that algebra is the doorway and gateway for future success of students in many aspects, including high school graduation, attending and success in college, and professional earning power. And the most important key to students’ success in algebra is their readiness. This book is not only a program that addresses algebra readiness; it is also a fundamental reform effort, based on the National Mathematics Advisory Panel’s (NMAP’s) Final Report (spring, 2008). The book approaches mathematic skills deficiencies on an individual basis, much like an IEP addresses the individual needs of a student with disabilities. The Reaching Algebra Readiness (RAR) process consists of four components: (1) Diagnostic, assessing student’s mastery of the skills needed to take algebra; (2) Prescriptive, developing an individualized plan to address specific math deficiencies; (3) Intervention, utilizing tools and resources (parental involvement, effective teaching strategies, etc), to improve students’ mathematics skills; and (4) Drills and Effective Teachings Strategies, mathematics is a discipline and, simply, there is no way of avoiding practice and drilling in reaching algebra readiness, which can be enhanced significantly by implementing proven effective teaching strategies. The Reaching Algebra Readiness (RAR) process and the related materials presented in this book will be revolutionary in helping all students acquire the math skills needed for success in algebra and beyond. This book is a must-guide for math teachers, parents who home school, parents who are looking for solutions, and educators pursuing fundamental education reforms.